2020
DOI: 10.3389/fvets.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Clinical Investigation of the Safety and Adverse Effects of Pantoprazole in Hospitalized Ruminants

Abstract: Clinical safety data for the use of gastroprotectants in hospitalized ruminants is lacking. In human patients, multiple adverse effects are possible from the use of pantoprazole including hematologic and electrolyte abnormalities as well as anaphylaxis and edema. The medical records of all hospitalized cattle, goats, and sheep administered pantoprazole over an ∼5-year period were retrospectively analyzed for adverse effects. Seventy-nine eligible patients were observed. Hypomagnesemia was observed after pantop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…Although some cases of post pantoprazole administration anaphylaxis (22,23) and edema (24,25) have been reported in humans, these clinical signs were not observed in our population. While the aim of this study was not to evaluate the clinical safety of pantoprazole in calves, the lack of observed adverse effects correlate with previously reported pantoprazole use in ruminants for case management of cattle (4,26), camels (27), sheep (15,28), yaks (29), and goats (30,31). Adverse effects of pantoprazole administration described people include hyponatremia (32), hypomagnesemia (33), as well as nephritis and hepatotoxicity (34).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although some cases of post pantoprazole administration anaphylaxis (22,23) and edema (24,25) have been reported in humans, these clinical signs were not observed in our population. While the aim of this study was not to evaluate the clinical safety of pantoprazole in calves, the lack of observed adverse effects correlate with previously reported pantoprazole use in ruminants for case management of cattle (4,26), camels (27), sheep (15,28), yaks (29), and goats (30,31). Adverse effects of pantoprazole administration described people include hyponatremia (32), hypomagnesemia (33), as well as nephritis and hepatotoxicity (34).…”
Section: Discussionsupporting
confidence: 52%
“…While our study did not report any adverse effect, it was not designed as a safety study. A retrospective study has suggested that pantoprazole may be safe to administer to hospitalized ruminants (15). Future prospective studies will be necessary to determine the clinical safety as well as the efficacy of pantoprazole in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, and in order to minimize potential adverse effects, such as gastric ulceration, the clients were instructed to observe for bruxism and melena. If suspicion of ulceration was noted, a gastroprotectant, such as ranitidine or pantoprazole could be administered ( 9 , 27 ), or meloxicam could be discontinued. Fentanyl has been used in both commercial and miniature pigs before ( 28 , 29 ), although limited data exists for adverse reactions with this practice.…”
Section: Discussionmentioning
confidence: 99%
“…As the mature bovine erythrocyte is approximately 5–6 μm in diameter ( 12 ) and the mature caprine erythrocyte is one of the smallest in domestic herbivores at approximately 3.39 μm in diameter ( 13 ), erythrocyte speciation is evident microscopically based on diameter as bovine erythrocytes are approximately 50% larger than caprine erythrocytes. Serum biochemistry results (BUN: Blood Urea Nitrogen; Creatinine; Total Bilirubin) were evaluated pre-transfusion, as well as 1 and 4 days post-transfusion by a validated biochemistry analyzer ( 14 ) at the Iowa State University Veterinary Clinical Pathology Laboratory. After the transfusion the goats were monitored for a 12-day period.…”
Section: Methodsmentioning
confidence: 99%